PENGARUH MINDFULLNESS-BASED COGNITIVE THERAPY (MBCT) TERHADAP DEPRESI PADA PASIEN DIABETES MELITUS - I Wayan Candra; Putu Epriliani (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2019)
This study aimed at knowing the effect of Mindfulness-Based Cognitive Therapy (MBCT) toward Depression of Diabetes Mellitus patients in Work Area Puskesmasn IV Denpasar Selatan in the year 2018. The design of this study used pra-eksperimental design with one-group pra-post test approach design. The samples were collected trough probability ramdom sampling type .The number of samples were 31 patients. The instrument of this study used Beck Depression Inventory-II (BDI-II). The result showed that there was significant effect (p=0,021 ) MBCT to patients Depression of Diabetes Mellitus in Puskesmas IV Denpasar Selatan in the year of 2018, that MBCT decrease the level depression of diabetic patients For this reason,. for next researcher it is suggested to develop this research about MBCT toward depression of patients with Diabetes Mellitus by used eksperimental design and increase the number of samples (30participants).